Interleukin-6 Receptor Blockade in Treatment-Refractory MOG-IgG–Associated Disease and Neuromyelitis Optica Spectrum Disorders. Issue 1 (January 2022) - Ringelstein, Marius; Ayzenberg, Ilya; Lindenblatt, Gero; Fischer, Katinka; Gahlen, Anna; Novi, Giovanni; Hayward-Könnecke, Helen; Schippling, Sven; Rommer, Paulus S.; Kornek, Barbara; Zrzavy, Tobias; Biotti, Damien; et al.
Abstract : Background and Objectives: To evaluate the long-term safety and efficacy of tocilizumab (TCZ), a humanized anti–interleukin-6 receptor antibody in myelin oligodendrocyte glycoprotein–IgG–associated disease (MOGAD) and neuromyelitis optica spectrum disorders (NMOSD). Methods: Annualized relapse rate (ARR), Expanded Disability Status Scale score, MRI, autoantibody titers, pain, and adverse events were retrospectively evaluated in 57 patients with MOGAD (n = 14), aquaporin-4 (AQP4)-IgG seropositive (n = 36), and seronegative NMOSD (n = 7; 12%), switched to TCZ from previous immunotherapies, particularly rituximab. Results: Patients received TCZ for 23.8 months (median; interquartile range 13.0–51.1 months), with an IV dose of 8.0 mg/kg (median; range 6–12 mg/kg) every 31.6 days (mean; range 26–44 days). For MOGAD, the median ARR decreased from 1.75 (range 0.5–5) to 0 (range 0–0.9; p = 0.0011) under TCZ. A similar effect was seen for AQP4-IgG+ (ARR reduction from 1.5 [range 0–5] to 0 [range 0–4.2]; p < 0.001) and for seronegative NMOSD (from 3.0 [range 1.0–3.0] to 0.2 [range 0–2.0]; p = 0.031). During TCZ, 60% of all patients were relapse free (79% for MOGAD, 56% for AQP4-IgG+, and 43% for seronegative NMOSD). Disability follow-up indicated stabilization. MRI inflammatory activity decreased in MOGAD ( p = 0.04; for the brain) and in AQP4-IgG+ NMOSD ( p < 0.001; for the spinal cord). Chronic pain was unchanged. Regarding only patients treated with TCZ for at least 12 months (n = 44), ARR reductions were confirmed, including the subgroups of MOGAD (n = 11) and AQP4-IgG+ patients (n = 28). Similarly, in the group of patients treated with TCZ for at least 12 months, 59% of them were relapse free, with 73% for MOGAD, 57% for AQP4-IgG+, and 40% for patients with seronegative NMOSD. No severe or unexpected safety signals were observed. Add-on therapy showed no advantage compared with TCZ monotherapy. Discussion: This study provides Class III evidence that long-term TCZ therapy is safe and reduces relapse probability in MOGAD and AQP4-IgG+ NMOSD.